Meeting other moms: Lesbian adoptive mothers' relationships with other parents at school and beyond. Issue 1 (2nd January 2018) - Goldberg, Abbie E.; Frost, Reihonna L.; Manley, Melissa H.; Black, Kaitlin A.
ABSTRACT: Little research has examined the friendships of lesbian parents, especially within the context of children's schools. This study of 40 lesbian adoptive parents (20 couples) focused on their relationships with other parents in the school community and how sexual orientation, race, and class dynamics impacted these relationships. Half of the participants described friendships with parents at the school, sometimes in spite of demographic differences, whereas others felt disconnected due to these differences. Outside of school, most participants reported friendships with other lesbian/gay parents. Parents who felt less connected to other parents at school tended to describe more lesbian/gay parent connections. Findings highlight the impact of life stage and context in shaping friendship patterns among lesbian parents.